Theory of value co-creation: a systematic literature review. Issue 6 (4th November 2014) - Gummesson, Evert; Mele, Cristina; Polese, Francesco; Galvagno, Marco; Dalli, Daniele
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to summarize and classify extant research and to better understand the past, present, and future state of the theory of value co-creation. Its main objectives are: to identify the different theoretical perspectives and research streams that characterize and define the co-creation literature, and to highlight the connections between them; to look for emerging trends and gaps in the literature by comparing the most recent papers with those representing the field's core. Design/methodology/approach – The paper relies on bibliometric data: co-citation techniques were employed to select, analyze, and interpret citation patterns within the co-creation literature. Findings – The paper identified two main clusters, as well as specific research streams and common themes, representing scholarly journals' publications on co-creation over the past years. These research streams and themes apply three different theoretical perspectives: service science, innovation and technology management, and marketing and consumer research. Data from the most recent publications has been used to verify if and how the original streams and themes are reflected in the contemporary debate. Research limitations/implications – Inevitably, the findings of the analysis have limitations related to the research design, the databases, and the applied bibliometric methods. Practical implications – From a practical perspective, the research impacts on theory building, management decision making, and teaching. Originality/value – This study depicts the remarkable development of the literature on co-creation and shows the latent structure underlying its different research streams. To the best knowledge, this study is the first to determine co-citation frequencies from both the SSCI and Scopus databases.